2018
DOI: 10.22159/ajpcr.2018.v11i11.28896
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Infertility Effects Test of Date Palm Fruit Extract (Phoenix Dactylifera L.) in Female Mice (Mus Musculus) Compared With Propolis

Abstract: Objective: The date palm (Phoenix dactylifera L) is one of the plants empirically used to increase fertility. The aim of this study was to compare the effect of ethanol extract of date palm fruit and propolis on fertility in female mice.Methods: 5 groups were assigned to 1 control and 4 experimental groups. The experimental group treated by oral administration of 100, 200 and 400 mg/kgBW of khalal date fruit extract and 200 mg/kgBW of propolis for 5, 10 and 15 days. Control groups received no extract. After 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Dates increase the level of estrogen in the blood plasma and help produce eggs properly because they contain vitamins (A, B) (Saryono and Rahmawati, 2016). A study conducted on female mice indicated that alcoholic date extract increases the number of follicles (ovarian follicles) and improves female fertility (Dillasamola et al, 2018).…”
Section: Fertilitymentioning
confidence: 99%
“…Dates increase the level of estrogen in the blood plasma and help produce eggs properly because they contain vitamins (A, B) (Saryono and Rahmawati, 2016). A study conducted on female mice indicated that alcoholic date extract increases the number of follicles (ovarian follicles) and improves female fertility (Dillasamola et al, 2018).…”
Section: Fertilitymentioning
confidence: 99%